Short‐term blood pressure changes have a more strong impact on stroke and its subtypes than long‐term blood pressure changes - Guo, Rongrong; Xie, Yanxia; Zheng, Jia; Wang, Yali; Dai, Yue; Sun, Zhaoqing; Xing, Liying; Zhang, Xingang; Sun, Yingxian; Zheng, Liqiang (Clinical cardiology (Mahwah, N.J.), 2019)
Background Elevated blood pressure (BP) is closely related to stroke and its subtypes. However, different time periods changes in BP may result in differential risk of stroke. Hypothesis Short‐term blood pressure changes have a more strong impact on stroke and its subtypes than long‐term blood pressure changes. Methods We designed the study on the effects of short‐ (2008‐2010) and long‐term (2004‐2010) BP changes on stroke events (2011‐2017), including 22 842 and 28 456 subjects, respectively. The difference in β coefficients between short‐ and long‐term BP changes on the effects of stroke were examined using the Fisher Z test. Results During a median 12.5‐year follow‐up period, 1014 and 1505 strokes occurred in short‐ and long‐term groups. In short‐term group, going from prehypertension to hypertension, the risk of stroke events increased (stroke: hazard ratio [HR] = 1.537 [1.248‐1.894], ischemic stroke: 1.456 [1.134‐1.870] and hemorrhagic stroke: 1.630 [1.099‐2.415]); going from hypertension to prehypertension, the risk of stroke events decreased (stroke:0.757 [0.619‐0.927] and hemorrhagic stroke:0.569 [0.388‐0.835]). Similarly, in long‐term group, going from prehypertension to hypertension, individuals had an increased risk of stroke (1.291, 1.062‐1.569) and hemorrhagic stroke (1.818, 1.261‐2.623); going from hypertension to prehypertension, participants had a decreased risk of stroke (0.825, 0.707‐0.963) and hemorrhagic stroke (0.777, 0.575‐0.949). Furthermore, the effects of BP changes during short‐term period on stroke events were greater than that in long‐term period. Conclusions Short‐ and long‐terms BP changes were both associated with the risk of stroke events. Furthermore, short‐term BP changes had a stronger impact than did long‐term changes on risk of stroke events.